Inclusion, organisational justice and employee well-being. Issue 6 (5th September 2016) - Huong, Le; Zheng, Connie; Fujimoto, Yuka
Abstract : Purpose: The purpose of this paper is to examine the relationship between employee perceived well-being and the four dimensions of organisational justice, namely, procedural, distributive, interpersonal and informational justice, and how dimensions of organisational justice affect employee well-being in the Australian tourism industry. Design/methodology/approach: The sample is selected from employees who work in the tourism industry in Australia, and the survey was conducted online ( n =121). Factor analysis is used to identify key items related to perceived organisational justice, followed by multiple regression analysis to assess the magnitude and strength of impacts of different dimensions of organisational justice on employee well-being. Findings: The results support the established view that organisational justice is associated with employee well-being. Specifically, informational justice has the strongest influence on tourism employee well-being, followed by procedural justice, interpersonal justice and distributive justice. Research limitations/implications: The authors acknowledge key limitations in the study such as a relatively small sample size and gender imbalance in the sample. Practical implications: The authors provide strategies for managers to increase levels of organisational justice in the tourism sector such as workgroup interactions, a consultation process, team culture and social support. Originality/value: This study builds on limited literature in the area of inclusion and organisational justice in tourism organisations. The study provides a new path to effective organisational management within the context of a diverse workforce, adding to the current debate on which dimensions of organisational justice contribute to improving employee well-being.